Răspuns:
Explicație pas cu pas:
a=[tex]7\frac{1}{2}[/tex]+[tex]3\frac{2}{3}[/tex]=[tex]\frac{15}{2} +\frac{11}{3}[/tex]
Aducem la acelasi numitor si devine [tex]\frac{45}{6} +\frac{22}{6} =\frac{67}{6}[/tex], deci a=[tex]\frac{67}{6}[/tex]
[tex]b=4\frac{1}{7} -3\frac{2}{3} =\frac{29}{7} -\frac{11}{3}[/tex]
Aducem la acelasi numitor si devine:
[tex]\frac{87-77}{21} =\frac{10}{21}[/tex]
deci b=[tex]\frac{10}{21}[/tex]
E=[tex]\frac{1}{3} + \frac{67}{6} -2*(\frac{10}{21} )[/tex]
=[tex]\frac{1}{3} +\frac{67}{6} -\frac{20}{21}[/tex]
=[tex]\frac{14+469-40}{42}[/tex]
=[tex]\frac{443}{42}[/tex]